First report of the genus Opostega Zeller, 1839 (Lepidoptera, Opostegidae) from China, with descriptions of two new species - Sun, Hao; Wang, Shuxia (Zootaxa, 2025)
The genus Opostega Zeller, 1839 is newly recorded from China. Opostega apicidissecta sp. nov. from Xinjiang and O. magnirotunda sp. nov. from Hainan are described as new. Images of adults and male genitalia are provided, along with a key to species of Opostega in the Palaearctic and Oriental regions. Additionally, the distribution of Opostegidae across China and neighboring countries is assessed.